Do financial markets allow the independence of central banks? - Damià Rey Miró; Pedro Piffaut; Ricardo Palomo Zurdo (Journal of Central Banking Theory and Practice, 2024)
The research work presented below addresses the possible concern of central bank independence through the development and application of econometric models. The complexity of the modelling has allowed a step further in corroborating that financial independence is not only linked to the appointments and pressures of the states regarding their economic policy but also the role that financial markets play by acting as a force that dictates and contaminates decisions of central banks. In this sense, the paper proposes a theoretical basis for recommendations on the application of the new monetary policy in a more complex environment, both due to the pandemic that was sweeping the world and the bulky debt that countries are carrying. The paper concludes with a series of measures and suggestions that could be addressed by monetary policymakers given the necessary but not easy normalization of monetary policy required at the global level.
Keywords: E58; E54; E52; E47; E32; C58; 330; Central banks; financial markets; monetary policy; forecasting and simulation; financial econometrics; business cycles; cointegration; co-integrated vector error correction model (VEC)